Study on the formation mechanism of intense rock pressure in fully mechanized top-coal caving mining under conditions of large burial depth and thick unconsolidated layer - Jindong, Wang; Jiayao, Fu; Shuchao, Guo (Frontiers in Earth Science, 2025)
Targeting the “two hard and one soft” overlying strata (fine sandstone, siltstone, and coal seam) of the 5th coal seam in Yanbei Coal Mine, Huating Mining Area, this study investigates the influence of key strata on strata movement and rock pressure during deep fully mechanized top-coal caving (FMTC) mining. A physical model using similar materials was conducted under three mining conditions: single working face mining, simultaneous mining of two working faces, and extended mining. Results showed that during single face mining, the key strata only bent and subsided without fracturing, leading to stable and mild pressure on the face. When two faces were mined simultaneously, the key strata fractured, causing sudden stress increases and intensified impact loads. In subsequent stages, pressure mainly depended on the suspended length of the key strata and the size of fractured blocks. The stope displayed a coexistence of “small structures”—formed by immediate roof breakage and controlling local strata damage—and “large structures”—formed by key strata breakage, which dominated pressure transfer and served as the main load-bearing system. The control range of the key strata was influenced by the face width and coal pillar section, with the presence or absence of a core area in the coal pillar being a decisive factor at a fixed width. Field practice in Yanbei Coal Mine confirmed that removing the core area from the section coal pillars effectively reduces the dynamic and static loads released by key strata failure, decreases the risk of intense rock pressure, and maintains the stability and safety of working faces during deep mining.